Travelook: mobile application to assist tourist by using Location-Based Service (LBS) / Muhammad Aizat Ibrahim - Ibrahim, Muhammad Aizat (Faculty of Computer and Mathematical Sciences, 2019)
Travel is a process of searching and identifying the destination including attractions places, restaurants, and accommodation during vacations. One of the emerging technology that available is location-based services, it is focus on providing information based on user’s position that has been located by Global Positioning System (GPS). Due to the growing number of devices, mobile application has been a major part for most of human being in this world, to make their lives easier. To create a mobile application by using location based services for tourists becomes a critical and need a lot of research. According to the survey that has been conducted, there are several problems that they usually faced such as they tend to overlooked some intresting places, lost during their vacation and felt cumbersome for accessing many sources to gather information. The principal aim of this research was to provide a mobile application to the tourist during their vacation. Moreover, user able to find a specific places based on the user location and get the places details. Other than that, user also able to calculate their budget for upcoming vacation in order to avoid from overspent. This application has been evaluated on functionality, usability and performance in order to make sure the application able to meet user requirement and expectation. For the future work, since the target user for this application is tourist, it can be a social media platform for tourist and share their vacation with friends. With the development of this application, more or less can help tourist during their vacation by maximizing the places that they can visit and keep their budget on track.